Construction of gen Z political insights after watching 'Bacapres Bicara Gagasan' on YouTube - Tabitha Hemastuti; Dasrun Hidayat; Zikri Fachrul Nurhadi; Nofha Rina (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
All Indonesians, especially Generation Z, need to be politically literate, as they are the ones who will shape the nation’s future. Since Generation Z constituted the majority of voters in the 2024 election, understanding their political insights is crucial. Despite their digital fluency, many Gen Z individuals remain disengaged from formal political processes. This study aims to analyze how Generation Z constructs political insight after watching the Bacapres Bicara Gagasan program on YouTube. Using a qualitative phenomenological method, this research explores their cognitive, affective, and personal integration experiences. The findings reveal that the program provided new perspectives on politics and influenced how Gen Z evaluates presidential candidates. The study underscores the importance of media, especially YouTube, in enhancing youth political awareness and participation in the digital age.